STUDENTS’ WRITING ERROR WRITTEN BY EIGHTH GRADE STUDENTS OF SMP JOSEPH KHATULISTIWA SINTANG - Ilinawati Ilinawati; Thomas Joni Verawanto Aristo; Yokie Prasetya Dharma; Ferdinanda Itu Meo; Shintia Monica Sari; Dwi Cahyadi Wibowo (STKIP Persada Khatulistiwa Sintang, 2023)
The background of this research is students’ errors in writing descriptive texts. The students do not understand the correct structure of writing descriptive text. The objective of this research is to find out the types of errors and to identify the dominant types of errors that found in students’ writing products. The subject of this research is the students’ writing descriptive text products written by eighth grade students of SMP Joseph Khatulistiwa Sungai Tebelian. This research used qualitative method, by classifying the errors using Surface Strategy Taxonomy. It consisted of four types of errors in the students’ writing descriptive text product. These were omission, addition, misformation and misordering. Qualitative data was collected from documentation of students’ writing descriptive text products. Qualitative data were analyzed through collection of a sample of learner language, identification of errors, description of errors and explanation of errors. The data analysis in this research was taken from 10 students of SMP Joseph Khatulistiwa Sungai Tebelian. The researcher analyzed 10 worksheets of students writing products. The researcher found the total of students’ errors were 46 errors of students errors. The finding showed there were four types of errors such as 26 errors of omission on percentage 57%, 12 errors of misformation on percentage 26%, 6 errors of addition on percentage 13%, and 2 errors of misordering on percentage 4%. The dominant type of error was omission with 27 errors.